Penerapan Media Interaktif Berbasis Heyzine dalam Pengajaran Geometri Bidang di Sekolah Dasar - Sandy Ihsan Amarulloh Ihsan; Puji Lestari (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2026)
Geometry learning, particularly plane geometry topics at the elementary school level, still faces various challenges, especially related to students’ understanding of abstract concepts and low learning motivation. Conventional instructional media that rely mainly on textbooks and verbal explanations are often insufficient to accommodate the learning characteristics of elementary school students who require concrete visualization and direct interaction. This study aims to examine students’ responses to the use of Heyzine flipbook-based interactive media in plane geometry learning at the elementary school level. This study employed a descriptive survey design involving a single class of second-grade elementary school students to evaluate students’ responses toward the implementation of Heyzine-based interactive media in plane geometry learning.The research instrument was a student response questionnaire covering aspects of presentation, content, and language. Data were analyzed using descriptive percentage techniques. The results showed that the Heyzine-based interactive media obtained a feasibility percentage of 93.33%, which was categorized as very feasible. Overall, these findings indicate that Heyzine flipbook-based interactive media can effectively support plane geometry learning and enhance students’ interest and conceptual understanding, future studies are recommended to investigate the effectiveness of Heyzine-based media on students’ learning outcomes through experimental research designs involving larger samples and different educational levels.